The Significance of Pancasila Values for Character Building from an Islamic Perspective - Arif Muzayin Shofwan (Yayasan Sinergi Kawula Muda, 2025)
Pancasila is the foundation of the Indonesian state, derived from various aspects of the nation's founding fathers, including Islamic teachings. This qualitative, literature-based research examines the significance of Pancasila values for character development within Islamic teachings. The data analysis technique used content analysis, selecting elements aligned with the research focus and objectives. This study found that Pancasila values for character development are significant to Islamic teachings: (1) Belief in the One and Only God is significant to Surah Al-Ikhlas verse 1, Surah An-Nahl verse 22, Surah An-Nahl verse 51, Surah Al-Baqarah verse 163, Surah Al-Isra verse 22, Surah Al-Kahf verses 1-4, and Surah Al-Mu'minun verse 91; (2) Just and civilized humanity is significant with Surah Al-Baqarah 213, Surah An-Nisa verse 135, Surah Al-Maidah verse 8, Surah Al-An'am verse 152, Surah Al-A'raf verse 29, Surah An-Nahl verse 90, Surah Al-Hujurat verse 13, Surah Al-Hadid verse 25, and Surah Al-Mumlahanah verse 8; (3) Indonesia's unity is significant with Surah Ali Imran verse 103, Surah Al-Hujurat verses 10-13, Surah Al-Anfal verse 46, Surah Yunus verse 19, Surah Hud verse 118, Surah An-Nahl verse 93, and Surah As-Shura verse 8; (4) Democracy led by wisdom in deliberation or significant representation with Surah Al-Baqarah verse 233 and Surah Ali Imran verse 159; (5) Social justice for all Indonesian people is significant with Surah Al-Baqarah verse 177, Surah An-Nisa verse 36, Surah Ali Imran verse 58, Surah An-Nahl verse 90, Surah Al-Isra verse 26, and Surah As-Shura verse 15.